Review and Prospect of Research on the Application of VR Technology in Education and Teaching Analysis based on citespace knowledge graphs - Zhang, Ximu; Liu, Yue (LPPM STIKI Malang, 2024)
This paper analyzes 863 China Knowledge Network (CNN) source documents using CiteSpaceV6.3.R1 software, and sorts out the current research status and development trend of VR technology in education and teaching by mapping the relevant knowledge map of keywords, issuing authors, and issuing institutions. It is found that the research on VR technology in education and teaching has experienced a slow growth from its start in 1996 to 2015, and then a significant growth after 2017 with interdisciplinary characteristics. In terms of authors and institutions, as the cooperation on this related topic is still small and very scattered, but there are some research teams cooperating with each other, and the research hotspots cover virtual reality, information technology, vr technology, education and teaching, and teaching tools. In the future, research in this field should show the following trends: deepen interdisciplinary integration and expand VR education applications; strengthen empirical research and verify the effectiveness of the technology; pay attention to ethical privacy and build a responsible education ecology.